О * -представлениях коммутационных соотношений с условиями ортогональности - Островская, Ольга Владимировна; Якимив, Роман Ярославович (My University, 2013)
В работе изучается категория интергрируемых *-предаставлений алгебр, порожденных соотношениями следующего вида. Доказано, что категория интегрируемых * -представлений изоморфна некоторой подкатегории категории представлений алгебры Кунца-Теплица. In this paper we study the categories of integra'ble * -representations of the family of * - algebras generated by relations of the following form. It is proved that the category of integrable representations of is isomorphic to the certain subcategory of the category of * -representations of Cuntz- Topeplitz algebra.
Keywords: коммутационные соотношения; Кунц-Теплиц; algebra (mathematics); commutation relations; Cuntz-Toeplitz; алгебра (математика); кафедра вищої математики імені проф. Можара В. І.